Predictors of mortality among Filipino patients with end-stage renal disease - Padilla, Benita S.
Background: Patients with end-stage renal disease (ESRD) are at high risk for mortality compared with the general population. The mortality rate of ESRD patients in the Philippines has not been adequately documented.Objective: The objective of the study were to determine the mortality rate and causes of death, and to identify factors which predict mortality among incident ESRD patients. Population: Three hundred twenty seven newly diagnosed ESRD patients at the National Kidney and Transplant Institute and the St. Luke's Medical Center were included in the study.Methods: In retrospective cohort design, patients were followed to death or the end of the study on June 30, 2003. Survival status was determined by review of hospital records, home telephone calls and home visits and procurement of death certificates from the National Statistics Office. Kaplan Meier survival analysis was used to describe the overall survival rate. Possible predictors of mortality were studied using Cox proportional hazards regression.Results: The estimated overall survival rate was 53% (95% CI: 47-58) at 12 months and 36% (95% CI: 30-42) at 12 months. More than half of the deaths occurred at home and most common causes of death were uremia, infectious and cardiovascular diseases. The most clinically useful model obtained on Cox proportional hazards analysis was that which included failure to start renal replacement therapy (RRT), belonging to the service group, increasing age, decreasing serum albumin and increasing Charlson comorbidity index score as predictors of mortality.Conclusions and Recommendations: The survival rate of ESRD patients in the Philippines was much lower than those reported in Western literature. There are indications that socioeconomic factors play an important role and these should be investigated further in future studies. Since it is unlikely that the government can provide widespread and long-term support for RRT programs, efforts should be directed at cost-effective programs which can lower the incidence of ESRD.